(untitled) (Communications in Computational Physics, 2020)
In land seismic exploration, strong near-surface heterogeneities can cause serious problems in seismic data acquisition and the quality of depth imaging. By introducing random velocity models to simulate velocity fluctuations in the near-surface layer and using the point spread function to characterize image quality, we examine how the scattering generated in near-surface heterogeneities can affect the subsurface image. In addition to the commonly known scattering noises which lower the signal to noise ratio in seismic data, our results also reveal that intermediate scale heterogeneities generate forward scattering which forms phase or travel time fluctuations. Due to intermediate-scale uncertainty in the shallow part of the migration velocity model, these phase changes are carried to the target by the extrapolated wavefields, breaking the zero phase image condition at the image point. This is a primary reason for deteriorated image quality in regions with strong near-surface scattering. If this intermediate-scale information can be obtained and built into the migration velocity, the subsurface image quality can be largely improved. These results can be the basis for further numerical investigations and field experiments. The proposed analysis method can also be used to evaluate other potential methods for dealing with near-surface scattering.